Rapid L2 Word Learning through High Constraint Sentence Context: An Event-Related Potential Study - Chen, Baoguo; Ma, Tengfei; Liang, Lijuan; Liu, Huanhuan (Frontiers in Psychology, 2017)
Previous studies have found quantity of exposure, i.e. frequency of exposure (Horst, Cobb, & Meara, 1998; Pellicer-Sánchez & Schmitt, 2010; Webb, 2008), is important for second language (L2) contextual word learning. Besides this factor, context constraint and L2 proficiency level have also been found to affect contextual word learning (Elgort, Perfetti, Rickles, & Stafura, 2015; Ma, Chen, Lu & Dunlap, 2015; Pulido, 2003; Tekmen & Daloğlu, 2006). In the present study, we adopted the event-related potential (ERP) technique and chose high constraint sentences as reading materials to further explore the effects of quantity of exposure and proficiency on L2 contextual word learning. Participants were Chinese learners of English with different English proficiency levels. For each novel word, there were four high constraint sentences with the critical word at the end of the sentence. Learners read sentences and made semantic relatedness judgment afterwards, with event-related potentials recorded. Results showed that in the high constraint condition where each pseudoword was embedded in four sentences with consistent meaning, N400 amplitude upon this pseudoword decreased significantly as learners read the first two sentences. High proficiency learners responded faster in the semantic relatedness judgment task. These results suggest that in high quality sentence contexts, L2 learners could rapidly acquire word meaning without multiple exposures, and L2 proficiency facilitated this learning process.